Single‐Cell Sorting of Non‐human Primate Adipocytes with Large‐particle Flow Cytometry. Issue 11 (4th November 2021) - Robino, Jacob J.; Kim, Yongwoon; Varlamov, Oleg
Abstract: Fluorescence‐activated cell sorting enables separation and analysis of heterogeneous cell populations based on size, granularity, and fluorescence intensity. Cell sorting has been widely used for isolation of cells that are ∼10 to 25 μm in diameter. By contrast, cell sorting of unilocular adipocytes isolated from white adipose tissue imposes a significant technological challenge. The combination of their large size (up to 200 μm) and the fragile nature of lipid‐laden adipocytes requires the use of specialized flow cytometers equipped with a large nozzle and capable of using low pressure to reduce shear forces during the cell sorting process. Furthermore, isolation of single adipocytes is rarely performed due to the lack of specialized cell sorters that can dispense single adipocytes into individual wells. Conducting cell sorting on single adipocytes would enable analyses of the cell‐autonomous heterogeneity in nutrient uptake and metabolism observed in white adipose tissue. In this protocol, we describe single‐cell sorting of rhesus macaque adipocytes labeled with fluorescent fatty acid and live‐cell indicators using large‐particle flow cytometry. This methodology represents a valuable resource for basic and translational studies aimed at understanding the development and function of adipocytes. © 2021 Wiley Periodicals LLC. Basic Protocol : Single‐cell flow sorting of adipocytes